2013
DOI: 10.1108/03074351311313834
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency analysis of exchange traded funds' pricing deviation

Abstract: PurposeThe purpose of this study is to extend the work of DeFusco, Ivanov and Karels by examining pricing deviation of DIA, SPY and QQQQ on intradaily basis.Design/methodology/approachThe DIA is designed to be one hundredth of the DJIA, the SPY is designed to be one tenth of the S&P 500 and QQQQ is designed to be one fortieth of the NASDAQ 100. This feature of ETFs requires the estimation of the difference between the proportional level of the index and the price of the ETF, which is the ETF pricing deviation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
8
2
Order By: Relevance
“…This paper extends the work of Ivanov (2014), Broom et al (2007), DeFusco et al (2011), Ivanov (2013, Bakshi et al (2003), Buraschi and Jackwerth (2001), Lakonishok et al (2004), Eraker et al (2003) and Wagner and Szimayer (2004). Ivanov (2014) examines the speculation-hedging relation in QQQ option markets around the QQQ move from AMEX to NASDAQ because there were improvements in its market trading efficiency after the move, as documented by Broom et al (2007).…”
Section: Literature Reviewmentioning
confidence: 55%
See 3 more Smart Citations
“…This paper extends the work of Ivanov (2014), Broom et al (2007), DeFusco et al (2011), Ivanov (2013, Bakshi et al (2003), Buraschi and Jackwerth (2001), Lakonishok et al (2004), Eraker et al (2003) and Wagner and Szimayer (2004). Ivanov (2014) examines the speculation-hedging relation in QQQ option markets around the QQQ move from AMEX to NASDAQ because there were improvements in its market trading efficiency after the move, as documented by Broom et al (2007).…”
Section: Literature Reviewmentioning
confidence: 55%
“…Studies by Eraker et al (2003) and Wagner and Szimayer (2004), among others, document that option implied volatilities change due to spot volatility jumps as the result of a specific underlying asset event, such as exchange move, which is in support of the Bakshi et al (2003) ideas. DeFusco et al (2011) and Ivanov (2013) study pricing deviation of the three most popular ETFs, one of which is QQQ. DeFusco et al study pricing deviation on daily basis by first defining it as the difference between the price of the underlying index and the price of the tracking ETF.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found by examining a sample of three leveraged ETFs in the Canadian market that these assets were generally traded by retail investors that hold their position for a noticeably short period, and that the deviations between ETF stock prices and its NAVs are small on average, but prone to increase. Ivanov (2013) expanded on the work by DeFusco, Ivanov and Karels (2011), and examined ultrahigh-frequency (one-minute intervals) price data from three major ETFs in the U.S market (DIA, SPY and QQQQ). The author found evidence of negative price deviation (discount) in the DIA and QQQQ prices in compared to the NAV, and of positive price deviation (premium) of SPY prices compared to the NAV of underlying assets, therefore, indicating arbitrage opportunities in the market.…”
Section: Previous Studies On Etfsmentioning
confidence: 99%